Effect of Rhythmic Craniocerebral Hypothermia on Morphological and Morphometric Features of Brain Tissue in Spontaneously Hypertensive Rats - Aidarova, Viktoria S. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 160